Pengaruh Audit Operasional, Pengendalian Internal, dan Good Clinical Governance terhadap Efektivitas Pelayanan Kesehatan pada Rumah Sakit Tipe B di Banda Aceh - Adinda Novia Sari; Riha Dedi Priantana (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2023)
This study aims to determine and analyze the effect of operational audit, internal control, and good clinical governance on the effectiveness of health services at type B hospitals in Banda Aceh. This research was conducted using a quantitative approach. The population in this study were all type B hospitals in Banda Aceh, totaling 3 hospitals and then using the census method by taking the entire population. Respondents in this study were all employe of the Internal Control Committee (SPI), accounting and finance divisions as well as medical services at three type B hospitals in Banda Aceh with a total of 98 respondents. The source of data in this study is primary data by distributing questionnaires. The data analysis technique used was multiple linear regression analysis with SPSS 25 application. The results showed that simultaneously and partially, operational audit, internal control and good clinical governance had an postive effect on the effectiveness of health services at type B hospitals in Banda Aceh.